2012
DOI: 10.1246/cl.2012.194
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Supramolecular Association of NCN-Pincer Pd-Complex-bound Norvaline Derivatives toward Fabrication of Controlled Metal Array

Abstract: Novel NCN-pincer Pd-complex-bound norvaline derivatives were synthesized. The N- and C-termini-alkylated Pd–norvalines spontaneously assemble into fibrous aggregates to form supramolecular gels, in which the NCN-pincer Pd complex moieties assemble in a highly oriented manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…However, there have been almost no investigations into amino‐acid‐based metal assembly except as detailed in our previous reports 35b. 37 We found that the N ‐ and C ‐alkylated Pd‐bound norvalines L ‐ 2 37a and L ‐ 4 showed excellent self‐assembly in various aromatic solvents to afford supramolecular gels. Figure 5 shows the typical gelation experiment for L ‐ 4 .…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…However, there have been almost no investigations into amino‐acid‐based metal assembly except as detailed in our previous reports 35b. 37 We found that the N ‐ and C ‐alkylated Pd‐bound norvalines L ‐ 2 37a and L ‐ 4 showed excellent self‐assembly in various aromatic solvents to afford supramolecular gels. Figure 5 shows the typical gelation experiment for L ‐ 4 .…”
Section: Resultsmentioning
confidence: 75%
“…This occurs because the intermolecular π–π interactions dominate the assembly of 1 and L ‐ 2 in DMF solution, where the formation of hydrogen bonds is suppressed. Indeed, in the crystalline state of 1 , the β‐sheet‐type self‐assembled structure found in the supramolecular gel of L ‐ 2 was not observed 37a. In contrast, for L ‐ 2 , a unique dimeric structure wrapped with undecyl alkyl chains was found, in which the π–π interaction between two PdCl(dpb) units binds up two molecules of L ‐ 2 and the dimer units are connected to each other through hydrogen bonding to form a chain‐like aggregate.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The geometrical parameters around the metal centres in these complexes, summarised in Table , are mostly unexceptional. One notable feature is the significant deviation from typical square‐planar coordination of the palladium(II) and platinum(II) centre, as shown in the side views (Figure S3) along with the small C6‐M‐Cl angles (155.3(2)–157.4(3)°). The deformation may be ascribed to steric repulsion between the chlorine atom and the two phenyl rings .…”
Section: Figurementioning
confidence: 99%